Comfort character of landscape features of traditional streets in Amman, Jordan - Alamoush S.J.; Ja'afar N.H.; Elina Mohd Husini; Wan Norisma Wan Ismail (Malaysian Institute Of Planners, 2024)
Indexed by Scopus